SARAK OPAT: LEADERSHIP STYLE IN GAYO COMMUNITY - Abidah; Al Misry; Septia Wahyuni; Susidamaiyanti; Lukmannulhaqim (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2021)
The paper discusses Sarak opat. Sarak opat is a leadership perform in the Gayo people. Sarak opat is a leadership behavior and practice. The approach of the research is ethnography. Research techniques with special involvement when a leader giving a speech. The analysis review field notes in the cultural symbols attached to traditional forms. The study shows that the leadership of the Gayo people does not have a lower hierarchy and has a unique rectangular shape. Behavioral leaders must have communication intelligence. The leader's expression characterizes accuracy, analogy, and kindness. Leaders are advanced, religious, fair, wise, honest, consistent, and frugal. The leader in Gayo local wisdom is the main decision maker (lantak uluh), administrator (tetah tentu), mentoring (jege perala), and honorable (layak laku).